Campylobacterota dominate the microbial communities in a tropical karst subterranean estuary, with implications for cycling and export of nitrogen to coastal waters. (14th September 2021) - Huang, Laibin; Bae, Hee‐Sung; Young, Caitlin; Pain, Andrea J.; Martin, Jonathan B.; Ogram, Andrew
Summary: Subterranean estuaries (STEs), the zones in which seawater and subsurface groundwater mix, are recognized as hotspots for biogeochemical reactions; however, little is known of the microbial communities that control many of those reactions. This study investigated the potential functions of microbes inhabiting a cenote and an offshore submarine spring (Pargos) in the near‐coastal waters of the Yucatan Peninsula, Mexico. The inland cenote (Cenote Siete Bocas; C7B) is characterized by a chemocline that is host to an array of physicochemical gradients associated with microbial activities. The chemocline includes an increasing gradient in sulfide concentrations with depth and a decreasing gradient in nitrate concentrations. The microbial community within the chemocline was dominated by Sulfurimonas and Sulfurovum of the Campylobacteria, which are likely responsible for sulfide oxidation coupled with nitrate reduction. Although C7B has not been directly connected with Pargos Spring, water discharging from the spring has physicochemical characteristics and microbial community structures similar to C7B, strongly suggesting biogeochemical processing in the STE impacts groundwater composition prior to discharge. This work yields insight into the microbial communities and biogeochemical reactions in STEs in karstic aquifers and provides evidence for the importance of Campylobacteria in controlling nitrate concentrations exported to marine springs.